(untitled) (Madhyabindu Journal, 2022)
The aim of this study was to explore the effect of service quality and customer satisfaction on consumer loyalty in internet banking in the case of the Nawalpur district. The basis for this study was established in its dimensions: they include easy to use, efficiency, security, reliability, and responsiveness. The study also aimed to recognize the elements that influence quality of service along with the concept and importance of service quality in online banking in particular. The study was based on the quantitative research design and the participants in this study were the bank’s customers using Internet services. The sample size for this study was maintained at 172 participants. To evaluate the phenomenon of the survey, a closed questionnaire of 5 points on a Likert scale was formulated. The results of this study indicated that there is a significant positive impact of service quality and customer satisfaction on the customer loyalty of Internet banking users in Nawalpur district. Therefore, the Nawalpur banking sector was advised to pay particular attention to all dimensions of the e-service quality and to customer satisfaction.